EXPLORING THE PREDICTORS OF PHYSICAL ACTIVITY AND HEALTH-PROMOTING LIFESTYLES IN URBAN AND RURAL AREAS (International Journal of Food and Nutritional Sciences, 2022)
Engagement in physical activity constitutes a fundamental component of a salutary lifestyle, and a considerable body of scientific inquiry has elucidated its myriad advantages. Consistent participation in exercise has been demonstrated to augment cardiovascular health, bolster psychological well-being, and facilitate efficient weight regulation. However, the attitude of urban and rural populations toward physical activity and healthy lifestyle may be different due to varying environmental, cultural, and socioeconomic factors. Higher population density, more health care accessibility, and infrastructure that supports more active lifestyles all usually make for urban areas where the opportunities for participation in exercise are greater. This study explores the perceptions and attitudes toward physical activity and healthy living among urban and rural populations, focusing on the factors influencing these attitudes. The investigation delineates the variances in perspectives regarding physical activity and health-enhancing lifestyles among inhabitants of urban and rural locales. Furthermore, the research explores the correlation between attitudes towards physical activity and health-promoting behaviors, evaluating the extent to which the living environment serves as a predictor of these attitudes and lifestyle decisions. The study elucidates the distinctions in viewpoints pertaining to physical exercise and health-promoting lifestyles among residents of urban and rural settings. Moreover, the inquiry investigates the relationship between perceptions of physical activity and health-enhancing behaviors, assessing the degree to which the residential environment functions as an indicator of these perceptions and lifestyle choices. Findings revealed significant differences between urban and rural participants in all aspects of attitudes toward physical activity. Variations were similarly noted in the physical activity subcategory of health-promoting lifestyles, alongside health responsibility and stress management dimensions. A significant and positive correlation was identified between individuals' attitudes toward physical activity and health-promoting lifestyle components. Furthermore, the physical activity s sub variable of the health-promoting lifestyle positively influenced attitudes toward physical activity. Additionally, the health responsibility sub variable impacted attitudes toward physical activity in areas such as social experience, health and fitness, risk-taking, thrill-seeking, Ascetic Experience and ascetic experience. Finally, the living environment was found to be a significant predictor of risk-taking, thrill-seeking, physical activity, spiritual growth, and interpersonal relationships.